2016
DOI: 10.1063/1.4941041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of line defects on spin-dependent electronic transport of zigzag MoS2 nanoribbons

Abstract: The nonlinear spin-dependent transport properties in zigzag molybdenum-disulfide nanoribbons (ZMNRs) with line defects are investigated systematically using nonequilibrium Green’s function method combined with density functional theory. The results show that the line defects can enhance the electronic transfer ability of ZMNRs. The types and locations of the line defects are found critical in determining the spin polarization and the current-voltage (I-V) characteristics of the line defected ZMNRs. For the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Moreover, after unsaturated Mo(S) atoms at the lower (upper) edge, the row of Mo atoms after them shows the negative (positive) spin-density distribution. These investigations show that bridging line defects induce a little magnetic effect on the defect [28] and our obtained results about figure III′ show that the presence of Stone-Wales defect decreases the magnetic effect in the middle of edges and it can be seen that the distribution of spin-down electrons in the row of Mo atoms for the atoms placed after the lower edge has little increased.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Moreover, after unsaturated Mo(S) atoms at the lower (upper) edge, the row of Mo atoms after them shows the negative (positive) spin-density distribution. These investigations show that bridging line defects induce a little magnetic effect on the defect [28] and our obtained results about figure III′ show that the presence of Stone-Wales defect decreases the magnetic effect in the middle of edges and it can be seen that the distribution of spin-down electrons in the row of Mo atoms for the atoms placed after the lower edge has little increased.…”
Section: Resultssupporting
confidence: 65%
“…7, it has been shown that in all the structures, the conductance for spin-up and spindown electrons is not equivalent, so it demonstrates the magnetic characteristic in these structures. Such magnetic characteristic is expectable for non-defect structure [24,36], and it also is observed in the presence of Mo-Mo and S bridges [28]. In Fig.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…A number of approaches have been suggested to tailor the electronic structure of graphene to introduce an appreciable band gap, which has been reviewed recently. [11][12][13][14][15] Owing to the unique physical properties and potential applications in nanoscale devices, many other 2D atomically thick materials, such as graphdiyne sheet, 16 silicene, 17,18 phosphorus 19,20 and layered transition-metal dichalcogenides 21,22 have attracted intensive attentions. The mono-layer boron nitride (BN) sheets known as hexagonal boron nitride (h-BN) have been fabricated in experiments 23,24 in 2009.…”
Section: Introductionmentioning
confidence: 99%